Charismatic leadership in organizations - Conger, Jay Alden; Kanungo, Rabindra Nath. (Thousand Oaks, Calif. ; London : SAGE, 1998)
Integrating the growing body of research and theory on the subject, this volume presents a comprehensive model of the charismatic leadership process.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Executive ability; Leadership; Organizational effectiveness